The Productivity Slowdown: The Culprit at Last? Follow-Up on Hulten and Wolff - Wolff, Edward N. (American Economic Review, 1996)
Charles R. Hulten's (1992) article suggested that very little of the productivity slowdown of the 1970's could be attributed to capital-embodied technical change. Hulten estimated that about 20 percent of total technical change (what he termed the residual growth of quality-adjusted output) in U.S. manufacturing over the period from 1949 to 1983 could be ascribed to embodied technical change in machinery and equipment. However, he found very little difference in the contribution of embodied technical change to total technical change between the periods 1949-1973 and 1974-1983, the slowdown period. In my paper (Wolff, 1991), I found a very significant vintage effect, estimated by the change in the average age of the capital stock. My data, drawn from Angus Maddison (1982), covered the G-7 countries over the period 1880-1979 and were based on figures for total capital (structures, machinery, and equipment) and for the entire economy. These results suggested that embodied technical change played a significant role in the productivity falloff of the 1970's. In this paper, I use more recent data for six OECD countries (France, Germany, Japan, the Netherlands, the United Kingdom, and the United States) compiled by Angus Maddison (1991, 1993a, b) and focus on the period from 1950 to 1989. I find here that the vintage effect is, indeed, a very strong determinant of the post-1973 productivity slowdown among OECD countries, explaining on average about two-fifths of the slowdown. The effect varies among countries, from a low of 23 percent in Japan to 69 percent in France. For the United States, the vintage effect appears to account for a little over half of its slowdown. Though it should be stressed that my results do not directly contradict those of Hulten, whose measure of technical change was confined to machinery and equipment within U.S. manufacturing, I will still attempt some reconciliation of my findings with those of Hulten at the end. The discrepancy in results suggests the possibility that the slowdown in investment in public infrastructure after 1973 may have played an important role in the post-1973 productivity slowdown. Moreover, since this is only a note, I will not review the rather extensive literature on the productivity slowdown of the 1970's (see, for example, Edward F. Denison's [1979] and my [Wolff, 1985] review articles), except to list a number of factors that have been examined. The main candidates have included the slowdown in the rate of capital formation, changes in the composition of the labor force, the role of energy price shocks, declines in R&D spending (and/ or the productivity of R&D), changes in the composition of output (mainly, the shift to services), and increased government regulation. Of these, the decline in investment appears to have played a major role, explaining about a fourth to a third of the slowdown in U.S. productivity growth after 1973. In Section I, I present the basic data for the analysis. The basic regression results are presented in Section II. In Section III, I consider other possible factors that may have played a role in the productivity slowdown of the 1970's. Section IV provides a decomposition of labor productivity growth into its various sources, including a vintage effect, estimated by changes in the average age of capital. Section V analyzes the relative importance of each component in the falloff of productivity growth observed among OECD countries after * Department of Economics, New York University, New York, NY 10003. The author would like to express appreciation to Moses Abramovitz, Charles Hulten, and two anonymous referees for their comments and to the Sloan Foundation and C.V. Starr Center for Applied Economics at New York University for financial support.